THE IMPACT OF ENTREPRENEURIAL EDUCATION, VOCATIONAL SKILLS AND ENTREPRENEURIAL MOTIVATION TOWARD ENTREPRENEURIAL INTEREST - Yulianti Putri, Meri; faridah, anni; Yuliana, Yuliana; elida, elida; Yulastri, Asmar; Nor Aishah, Buang; Kumala Dewi, Fitrika (Jurnal Pendidikan Ilmu Sosial, 2025)
This research explores the impact of entrepreneurial learning, vocational skills and motivation in entrepreneurship on entrepreneurial interest of tourism, hospitality and engineering students at Universitas Negeri Padang. Using a quantitative research methodology, data was collected using a structured survey involving 43 students. The findings indicate that entrepreneurial interest is significantly and positively influenced by entrepreneurship education, vocational competence, and entrepreneurial motivation. Statistical analysis showed a high level of explanatory power, with a significance level of p = 0.000 and an adjusted R² value of 0.704, indicating a strong model fit. These results shows that education and skills training are crucial for increasing students entrepreneurial interest. This study underscores the need for higher education institutions, particularly in Indonesia, to strengthen entrepreneurship curricula, enhance vocational training, and foster motivational factors to better prepare students for entrepreneurial careers. By identifying the key drivers of entrepreneurial interest, this research contributes to the design of more effective educational strategies and policy interventions aimed at promoting youth entrepreneurship across different academic fields.